Constitutive expression of selected genes from the pentose phosphate and aromatic pathways increases the shikimic acid yield in high-glucose batch cultures of an Escherichia coli strain lacking PTS and pykF - Rodriguez, Alberto (BioMed Central, 2013)
BACKGROUND: During the last two decades many efforts have been directed towards obtaining efficient microbial processes for the production of shikimic acid (SA); however, feeding high amounts of substrate to increase the titer of this compound has invariably rendered low conversion yields, leaving room for improvement of the producing strains. In this work we report an alternative platform to overproduce SA in a laboratory-evolved Escherichia coli strain, based on plasmid-driven constitutive expression of six genes selected from the pentose phosphate and aromatic amino acid pathways, artificially arranged as an operon. Production strains also carried inactivated genes coding for phosphotransferase system components (ptsHIcrr), shikimate kinases I and II (aroK and aroL), pyruvate kinase I (pykF) and the lactose operon repressor (lacI). RESULTS: The strong and constitutive expression of the constructed operon permitted SA production from the beginning of the cultures, as evidenced in 1 L batch-mode fermentors starting with high concentrations of glucose and yeast extract. Inactivation of the pykF gene improved SA production under the evaluated conditions by increasing the titer, yield and productivity of this metabolite compared to the isogenic pykF(+) strain. The best producing strain accumulated up to 43 g/L of SA in 30 h and relatively low concentrations of acetate and aromatic byproducts were detected, with SA accounting for 80% of the produced aromatic compounds. These results were consistent with high expression levels of the glycolytic pathway and synthetic operon genes from the beginning of fermentations, as revealed by transcriptomic analysis. Despite the consumption of 100 g/L of glucose, the yields on glucose of SA and of total aromatic compounds were about 50% and 60% of the theoretical maximum, respectively. The obtained yields and specific production and consumption rates proved to be constant with three different substrate concentrations. CONCLUSIONS: The developed production system allowed continuous SA accumulation until glucose exhaustion and eliminated the requirement for culture inducers. The obtained SA titers and yields represent the highest reported values for a high-substrate batch process, postulating the strategy described in this report as an interesting alternative to the traditionally employed fed-batch processes for SA production.